Genome-wide identification of long noncoding natural antisense transcripts and their responses to light in Arabidopsis - Wang, Huan; Chung, Pil Joong; Liu, Jun; Jang, In-Cheol; Kean, Michelle J.; Xu, Jun; Chua, Nam-Hai

(untitled) (Genome Research, 2014)
Recent research on long noncoding RNAs (lncRNAs) has expanded our understanding of gene transcription regulation and the generation of cellular complexity. Depending on their genomic origins, lncRNAs can be transcribed from intergenic or intragenic regions or from introns of protein-coding genes. We have recently reported more than 6000 intergenic lncRNAs in Arabidopsis. Here, we systematically identified long noncoding natural antisense transcripts (lncNATs), defined as lncRNAs transcribed from the opposite DNA strand of coding or noncoding genes. We found a total of 37,238 sense–antisense transcript pairs and 70% of annotated mRNAs to be associated with antisense transcripts in Arabidopsis. These lncNATs could be reproducibly detected by different technical platforms, including strand-specific tiling arrays, Agilent custom expression arrays, strand-specific RNA-seq, and qRT-PCR experiments. Moreover, we investigated the expression profiles of sense–antisense pairs in response to light and observed spatial and developmental-specific light effects on 626 concordant and 766 discordant NAT pairs. Genes for a large number of the light-responsive NAT pairs are associated with histone modification peaks, and histone acetylation is dynamically correlated with light-responsive expression changes of NATs.